Analisis Sektor Ekonomi Unggulan Kabupaten Tasikmalaya Tahun 2010-2021 - Prasetyo, Rizki Maulana; Hamzah, Risna Amalia (Jurusan Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Siliwangi, 2022)
This study examines Klassen typology in Tasikmalaya Regency by identifying gross domestic regional bruto based on constant price 2010 to measure one of the superior sectors between 17 sectors interpreted in Tasikmalaya Regency from 2010-2021. Tasikmalaya Regency has numerous potentials especially in agriculture. Tasikmalaya Regency has significant hectares for agriculture. To interpret another numerous potentials, the methods of Klassen typology result must contain the superior sector as primary indicator to adequate coherency between agricultural and other commodities produced in Tasikmalaya Regency. Another potential of Tasikmalaya Regency is in extensive trades, and industries by identifying the amount of GDRP coherently and amount of industries such as the rectification industry of animal skins, chemical, tools, tobacco, and boutique. The methodology of research is using Klassen typology by measuring 17 sectors in gross domestic regional product based on constant price 2010. The criteria of Klassen typology are interpreted by indicating each of the contribution sectors and the growth of the economy in each sector in GDRP and stratified to four segments that contains prime sector, growth sector, potential sector, and underdeveloped sector. The result of this research indicates Tasikmalaya Regency has superior commodities in agriculture, extensive trades, information and communication, monetary and insurance, real estate, company services, and education.Penelitian ini mempelajari tentang tipologi Klassen di Kabupaten Tasikmalaya dengan mengidentifikasi produk domestik regional bruto atas dasar harga konstan tahun 2010 untuk mengukur sektor unggulan di antaranya 17 sektor ekonomi di Kabupaten Tasikmalaya tahun 2010 sampai 2021. Kabupaten Tasikmalaya memiliki banyak potensi khususnya pada sektor pertanian, dimana Kabupaten Tasikmalaya memiliki lahan yang luas untuk melakukan kegiatan pertanian. Untuk menginterpretasikan potensi lainnya di Kabupaten Tasikmalaya, hasil dari analisis tipologi Klassen harus menunjukkan sektor unggulan lainnya di bidang pertanian atau sektor lainnya di Kabupaten Tasikmalaya seperti perdagangan besar dan industri dengan mengidentifikasi dari jumlah PDRB dan jumlah industri kulit, kimia, peralatan, tembakau, dan batik. Metode penelitian yang digunakan adalah tipologi Klassen dengan mengukur 17 sektor dalam PDRB dan diklasifikasikan ke dalam beberapa segmen seperti sektor prima, sektor berkembang, sektor potensial, dan sektor terbelakang. Hasil dari penelitian ini menunjukkan bahwa Kabupaten Tasikmalaya memiliki potensi unggulan di sektor pertanian perdagangan besar, informasi dan komunikasi, jasa keuangan dan asuransi, real estate, jasa perusahaan, dan pendidikan.